Strategi Televisi Lokal Dalam Mempertahankan Eksistensi Bahasa Daerah - Solekhah, Ayu; Duku, Sumaina; Yahya, Ahmad Harun (Jurnal Ilmu Sosial, Humaniora dan Seni, 2023)
Thesis entitled "Local Television Strategy in Maintaining the Existence of Regional Language (Descriptive Study of Grebek Palembang TV (PALTV) News Program). This research aims to see how the strategy used by Palembang TV in maintaining the existence of local languages through the Grebek crime news program, using the theory of Media Ecology by Dimmick and Rothenbuhler to maintain its existence, the media needs three life supports, namely: capital (income), types of content (types of media content) and types of audience (types of audiences). And the supporting and inhibiting factors experienced by PALTV in delivering regional language news. The method applied in this research is descriptive qualitative and data collection techniques with interviews, observation and documentation with all those related to the research. The results of this study show that the strategies implemented by PALTV in maintaining local regional languages are: 1) implementing program strategies on the Grebek news program by covering program planning, strategies in program production and purchasing, positioning program schedules in accordance with audience habits and carrying out program monitoring and evaluation. 2) strategies to capture the audience market on the Grebek news program by including carrying out audience segmentation, sorting target audiences, forming audience perceptions through taglines. 3) marketing strategies in marketing the Grebek program (working together with the local media) Palembang TV has joined satellite and satellite dish services that can be accessed through the YouTV application, the enthusiasm and desire of the crew to advance Palembang TV. And the inhibiting factors are finding sources and limited tools, language translators when making scripts, and health.